The effect of COVID-19 and COVID-19 vaccines on chronic spontaneous urticaria: single center experience - Öner Özdemir; Ümmügülsüm Dikici (Alergologia Polska)
Chronic spontaneous urticaria (CSU) is known by spontaneous urticarial lesions and/or angioedema resisting ≥ 6 weeks. It is reported that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) enters the body and triggers urticaria and angioedema, and even might cause CSU. Although coronavirus disease 2019 (COVID-19) vaccines do not generally affect CSU patients, it has been observed that they occasionally exacerbate the disease. Here, we studied COVID-19, COVID-19 vaccines, and their effects on CSU cases. The records of 16 cases who mostly took omalizumab due to being resistant CSU cases were retrospectively reviewed. There was no problem with an inactivated (Sinovac ® ) vaccine. After mRNA (BioNTech ® ) vaccination, 2 of our patients had an exacerbation and even one had to switch to omalizumab. In 2 patients, CSU developed despite the absence of an urticaria-angioedema history and they were also unresponsive to standard antihistamine therapy and therefore had to be started on omalizumab. As a result, omalizumab had to be started in 3/8 patients after mRNA vaccination due to CSU exacerbation or treatment failure. It should be also kept in mind that SARS-CoV-2 infection and vaccination against it may exacerbate or trigger the disease in some patients.